Noise analysis of grinding machine in the material cutting process - Dharmastiti, Rini; Wijaya, Andi Rahadyan; Kurniasari, Fitri (Jurnal Teknosains, 2025)
The handheld grinding machine used for cutting materials has generated noise that may affect the operator and individuals nearby. The noise produced by this machine needs to be analyzed to prevent potential health impacts. This study aims to measure the noise levels the handheld grinding machine generates while cutting materials such as ceramic, metal, and natural stone. Noise measurements were taken at the noise source and distances of 2 meters, 3 meters, and 4 meters from the source. A sound level meter was used for the noise measurements. The study's results indicate that the type of material being cut using the handheld grinder does not significantly affect the noise level produced. The highest noise level was recorded when cutting the plate, with an equivalent continuous sound level (Leq) of 91.6 dB at the source. The lowest noise level was recorded when cutting ceramic material, with a Leq of 89.7 dB. Statistical tests on the distance and measurement locations at 2 meters, 3 meters, and 4 meters from the source showed that the distance does not significantly affect the noise level. At distances of 2 meters and 3 meters, the average Leq for all materials was the same, ata 94.2 dB, while at 4 meters, the average Leq was slightly lower, at 93.9 dB.